Structural and Electron Spin Resonance analysis of Eu3+ doped Borotellurite Glass containing Manganese Oxide Nanoparticles - Siti Maisarah, Aziz; Nurulhuda, Mohammad Yusoff; Salmiah Jamal, Mat Rosid (2019)
Structural properties of 30B2O3-(59-x)TeO2-10MgO-xEu2O3-1Mn3O4 glass are prepared via melt quenching method. The glass samples are characterized by X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR) Spectroscopy and Electron Spin Resonance (ESR) Spectroscopy. The glass nature is confirmed by XRD pattern. FTIR spectra display a shift in vibrational modes of TeO4 and TeO3 units thus indicate an alteration in the glass network structure due to an incorporation of Eu2O3. Influence which varies Eu2O3 concentrations on the structural due to the nature of spin-spin interaction are determined. Both g value and resonance magnetic field (Hr) are found to be in the range of (189-198) and (211-226) Oe respectively. The obtained g value of glass samples will modify the structural of europium doped magnesium borotellurite glass due to this presence of manganese oxide nanoparticles (Mn3O4 NPs) which may be useful for developing efficient photonic devices.